ANALISIS KESALAHAN BERBAHASA DALAM KARANGAN SISWA KELAS X AK 3 SMK NEGERI 1 KOTA JAMBI - Tuti Mardianti; Imam Suwardi Wibowo; Maizar Karim (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2016)
ABSTRACT This research is to describe the form of error in the language of class X students of AK 3 SMK Negeri 1 Kota Jambi in terms of spelling, affix, reduplication, word wastage, and diction. The approach and type of research used in this research is descriptive qualitative. Research data in the form of language errors contained in the student essay. Sources of research data is the essay of students of class X AK 3 SMK Negeri 1 Kota Jambi Academic Year 2014/2015. Technique of data collecting done by using method of documentation. After the essay is read, the essay is carefully researched to find the error language that will be used as data. The results of the analysis of language errors in student essay can be summarized as follows: (1) errors of language often found in student essay is a spelling mistake. Spelling errors occur due to improper writing of words, capital letters, italics, number symbols, and punctuation, (2) affix errors found in the use of prefixes, prefixes in-, confix, confix , and the confix is ​​that (3) the reduplication error occurs because of the use of an incorrectly coupled word (4) the waste of words occurs because there is still a lot of usage of words that do not really need to be used (5) the error of diction occurs because the selection of words that do not right. Keyword: essay, language error